Pengaruh Kemampuan Digital dan Kualitas Layanan Elektronik Terhadap Minat Beli Melalui E-Commerce - Shinta Khairunnisah; Afif Zaerofi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Currently, the world is experiencing rapid changes with the advent of the Fourth Industrial Revolution. Digital technology is rapidly developing worldwide, including in Indonesia. Technological advancements have permeated all human activities, including the business world, through innovations in electronic commerce, commonly known as e-commerce. This research uses descriptive quantitative research methods and approaches. The study employs Partial Least Squares-SEM as a tool to analyze data obtained from distributed questionnaires. Data was collected through random sampling distribution of questionnaires to respondents, specifically students in Bogor who have shopped on e-commerce platforms. The results of this study indicate that the variable of digital capability has a positive and significant effect on purchase intention, as evidenced by an Original Sample value of 0.152 and a P-value of 0.027 < 0.05. Additionally, the quality of electronic services has a positive and significant effect on purchase intention, as seen from an Original Sample value of 0.640 and a P-value of 0.000 < 0.05.